math

posted by .

(6a^4b+ab^3)+(3ab^3-6a^4b)

  • math -

    Combine the like terms
    (6a^4b - 6a^4b) + (ab^3 + 3ab^3)
    = 0a^4b + 4ab^3
    = 4ab^3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    What is the value of a in terms of b? 3ab=6 Divide both sides of that equation by 3b to get an equation with only a on one side. Convert the 6/3 to a 2. 3ab=6 ab =2 a =2/b
  2. math

    ab-2cd/-3ab-6cd simplify?
  3. math

    what is the answers to the following: 2x to the second power-3ab+27
  4. christ maths

    3ab+2a+5b
  5. math help

    If 3ab=6, what is the value of a in terms of b?
  6. Math

    Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B.) 8a^4 b^3 + 6a^3 b^5 - 2a^3 b^4 C.) 8a^4 b^3 + 6a^3 b^5 + 2a^3 b^4 D.) 8a^4 b^5 + 3a^3 b^5 + 2a^3 b^4 I'm guessing its A
  7. math 1 question!!!!!!

    Which is equivalent to the expression shown when a > 0 and b > 0?
  8. algebra

    (-a-6b +4)3ab The answer I got was 3(-a-6b+4)ab
  9. Math

    I just want to make sure I have done this correctly. (10a^3b)(3ab^2c^2) = 30a^4b^3c^2
  10. Math Vector

    ABCDEF is a regular hexagon. Show that vecotr AB+AD+FA+EA=3AB

More Similar Questions